THE PROVISION OF E-SERVICES IN THE EDUCATION SECTOR - WARZOCHA, Tomasz (Trends in education, 2014)
The article was presents issues related to education in the information society, service provided by means of electronic services - e-services. In article was present some examples of e-services support the educational process.
Keywords: education; new technologies; the educational process; information society; e-services; e-learning.